2014
DOI: 10.1371/journal.pone.0099089
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve and Interobserver Agreement of Confocal Laser Endomicroscopy for Detecting Precancerous or Early-Stage Esophageal Squamous Cancer

Abstract: BackgroundConfocal laser endomicroscopy (CLE) can provide in vivo subcellular resolution images of esophageal lesions. However, the learning curve in interpreting CLE images of precancerous or early-stage esophageal squamous cancer is unknown. The goal of this study is to evaluate the diagnostic accuracy and inter-observer agreement for differentiating esophageal lesions in CLE images among experienced and inexperienced observers and to assess the learning curve.MethodAfter a short training, 8 experienced and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
4
23
0
1
Order By: Relevance
“…Novice observers reached moderate levels of agreement in this study (κ = 0.55) . Another study in detecting precancerous or early‐stage esophageal squamous cancers found overall substantial agreement among experienced and novice users alike . We achieved similar results, with overall substantial agreement being achieved among users of varying experience levels in both our image and video sets after uniform, brief, self‐guided, training describing specific image criteria.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Novice observers reached moderate levels of agreement in this study (κ = 0.55) . Another study in detecting precancerous or early‐stage esophageal squamous cancers found overall substantial agreement among experienced and novice users alike . We achieved similar results, with overall substantial agreement being achieved among users of varying experience levels in both our image and video sets after uniform, brief, self‐guided, training describing specific image criteria.…”
Section: Discussionsupporting
confidence: 74%
“…Talreja et al demonstrated substantial agreement with improved diagnostic accuracy in a follow‐up study that incorporated a standardized classification system and a single teaching session . Liu et al demonstrated a similar quick learning curve when agreement (κ) was significantly higher in the experienced group over the inexperienced group in only the first set of four image sets . Although we did not directly test for learning curve, we believe that we achieved substantial agreement due to pretest training using predefined image classification criteria.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition to this there is a learning curve required to interpret the images that are vastly different from traditional endoscopic images. One study estimated an average learning curve of 35 cases required to interpret post-procedural CLE images with 93% accuracy [47,48]. Case selection will be key in maximizing outcomes obtained from this modality.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The overall 5-year survival rate is about 15 to 25 %, and the outcome depends on whether it is diagnosed at the early stage [1]. The two most common types of esophageal cancer are esophageal adenocarcinoma (EADC) and esophageal squamous cell carcinoma (ESCC) [2], and the latter is the predominant one in China [3].…”
Section: Introductionmentioning
confidence: 99%